Legal Reformulation of Coastal Land Utilization for Beach Club Businesses as a Support for Sustainable Tourism in Bali - Ni Nyoman Sri Puspadewi; Johanes Ibrahim Kosasih; I Ketut Kasta Arya Wijaya (JURNAL AKTA, 2026)
The rapid growth of beach club enterprises along Bali’s coastal areas reflects the ongoing transformation of tourism from a cultural-spiritual model toward a commercial paradigm that often disregards ecological, social, and cultural dimensions. The use of coastal land as business space is not merely an economic or spatial planning issue; it also deeply engages with the religious-magical values of Balinese society, which are grounded in the Tri Hita Karana philosophy. However, within the framework of national law, beach clubs have yet to be recognized as a distinct business entity, neither under Law No. 10 of 2009 on Tourism, Law No. 26 of 2007 on Spatial Planning, nor within the KBLI classification system or the OSS-RBA licensing mechanism. This legal vacuum creates room for the exploitation of coastal areas, leading to conflicts of interest among investors, indigenous communities, and the environment. Through a normative and socio-juridical approach, this study proposes a comprehensive regulatory formulation, including the addition of a specific business classification within national tourism policy, revision of the KBLI, and the establishment of local zoning regulations for coastal areas that are participatory and rooted in local wisdom. The findings highlight the importance of recognizing beach clubs as tourism-supporting businesses that adhere not only to the principles of lex certa and lex scripta but are also in harmony with the social and spiritual fabric of Balinese society. This reformulation is expected to serve as a convergence point between legal certainty, environmental protection, and the sustainability of local culture in the pursuit of a holistic and just tourism development model for Bali.